Clinical Impact of Reperfusion Techniques and Occlusion Sites in Thrombectomy: Insights from the ASSIST Stroke Registry - Ulf Neuberger; Lori Lyn Price; Salvador Miralbés; Bharath Naravetla; Alejandro Spiotta; Christian Loehr; Mario Martínez‐Galdámez; Ryan A. McTaggart; Luc Defreyne; Pedro Vega; Osama O. Zaidat; David S. Liebeskind; et al. (Stroke: Vascular and Interventional Neurology)
Background Mechanical thrombectomy has changed the landscape of acute ischemic stroke treatment, offering improved outcomes for patients with large vessel occlusions. The interplay between reperfusion techniques and occlusion sites remains a critical consideration in treatment decisions. This study investigates the impact of primary reperfusion techniques—stent retriever classic, stent retriever combination with aspiration, and direct aspiration—on procedural and clinical outcomes at different occlusion sites. Methods Using data from the ASSIST registry, a prospective multinational initiative, patients with anterior circulation acute ischemic stroke with large vessel occlusions (n = 1477) were included. Three primary occlusion sites—M1 segment of the middle cerebral artery, M2 segment of the middle cerebral artery, and the internal carotid artery—were studied. Univariate tests and multivariable logistic regression models were used to assess associations between reperfusion techniques and procedural and clinical outcomes, including the expanded thrombolysis in cerebral infarction score and the modified Rankin Scale, stratified by occlusion site. Results Achieving expanded thrombolysis in cerebral infarction ≥2c after first pass was lower in internal carotid artery occlusions (18.2%, P<0.0001) with direct aspiration alone compared with stent retriever classic (38.2%) or stent retriever combination with aspiration (43.3%), while no differences were seen for M1 segment of the middle cerebral artery (P = 0.77) and M2 segment of the middle cerebral artery (P = 0.29) occlusions. Bailout maneuvers, which were more frequent in the direct aspiration group for all occlusion sites, did not result in longer procedure times or different final recanalization outcomes in direct aspiration compared with stent retriever classic or stent retriever combination with aspiration. Overall, there were no differences in the rate of patients with modified Rankin Scale scores of 0–2 at 90 days. No differences in safety outcomes were observed. Conclusions This study provides insight into the complex relationship between reperfusion techniques and occlusion sites in patients with acute ischemic stroke and shows that certain techniques have advantages in certain occlusion sites. As the field evolves, further research is warranted to refine our understanding of these dynamics and inform clinical practice.